Assessing the Vulnerability of an Aquifer to Climate Variability through Community Participation in Arivaca, Arizona. (5th January 2021) - Uhlman, Kristine; Eastoe, Chris; Guido, Zack; Crimmins, Michael A.; Purkey‐Deller, Anne; Eden, Susanna
Abstract: In Arivaca, Arizona, groundwater isotope measurements (stable O and H, tritium, and carbon‐14) were made in conjunction with water level measurements and climate data. Recharge is predominantly young (post‐1950) and is mainly from summer monsoon precipitation. Following a five‐month period of unusually low δ 18 O and δ 2 H in precipitation in 2014–2015, corresponding shift in groundwater δ 18 O and δ 2 H was observed only at a site with recently built gabions. Water levels near the basin outlet increase in summer following periods of high storm frequency. Water levels also rebound in winter, possibly because of cessation of transpiration. The young groundwater is vulnerable to climate change, e.g., to protracted periods with summers that are drier or hotter than normal. Rapid assessment of groundwater and its connection to climate can provide valuable information to local water managers and citizens for whom more expensive studies are not feasible. Such assessments, based on relatively inexpensive isotope analyses and groundwater level data collected by volunteers, engage the community in management of its water resources. In Arivaca, the community responded to the results of the assessment with heightened interest in managing their water for sustainability and the construction of gabions to increase recharge from stormwater.